PREFERENSI RISIKO SEBAGAI PEMODERASI PROGRAM PENGUNGKAPAN SUKARELA DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Fajriana, Icha; Wenny, Cherrya Dhia (Universitas Muhammadiyah Palembang, 2024)
This research aims to test the effect of voluntary disclosure programs, tax sanctions, and taxpayer awareness on individual taxpayer compliance with risk preferences as moderation variables. This research uses quantitative research methods. The population in this study is the individual taxpayer register in KPP Pratama Palembang Ilir Barat. The sample in this study was 100 respondent. The data analysis technique used is multiple linear regression analysis and moderated regression analysis with the help of the SPSS version 26 program. The results of this research show that voluntary disclosure have no effect on taxpayer compliance while taxpayer awareness have effect on taxpayer compliance. Risk Preference moderate the effect of voluntary disclosure program on taxpayer compliance, but risk preference doesn’t moderate the effect of Taxpayer Awareness on taxpayer compliance.